The Impact of Early Marriage on Stunting in Kutai Kartanegara - Urnia, Ega Ersya; Suryani, Heni; Cybronika, Lutfhi Metta Mediana; Putri , Rosalin Ariefah; Wahyuni, Rahmawati; Sari, Riana Trinovita; Sinaga, Elisa Goretti; Astuti, Dewi Rinda; Metasari, Andi Ria; Hidayati, Diah Ulfa (Sebatik, 2025)
In 2020, the prevalence of stunting in the world was 149.2 million or 22% in children under 5 years of age. Meanwhile, based on the results of the 2022 Indonesian Nutrition Status Survey, the prevalence of stunting in Indonesia is 21.6%. This figure is still relatively high, when compared with the target of reducing stunting to 14% by 2024. For the East Kalimantan Province region, the prevalence of stunting according to the 2022 Indonesian Nutrition Status Survey (SSGI) is 23.9%, while Kutai Kartanegara Regency is The region with the highest prevalence of stunted toddlers is in East Kalimantan in 2022, reaching 27.1%. The aim of this research is to analyze the impact of early marriage on the incidence of stunting in toddlers. The type of research that will be carried out uses quantitative research. The research is Cross Sectional with an observation approach or data collection at once at a time (point time approach). This research will be carried out in June 2024 which will take place in the Teluk Dalam Health Center Working Area. The population in this study is stunted toddlers in the Teluk Dalam Health Center Working Area which amounted to 121 people with a sample size of 32 people. The primary data processing obtained includes data entry, data processing and statistical data analysis is carried out by computerization, namely by using the SPSS program to conduct data analysis with descriptive analysis and inferential analysis, namely the Normality Test, Homogeneity Test, Chi Square Test. The results of the calculation of parents' knowledge about early marriage found that 65.6% of respondents had good knowledge and 3.1% had poor knowledge about early marriage. Meanwhile, the results of the calculation of parents' knowledge about stunting found that 62.5% of respondents had moderate knowledge and 9.4% had good knowledge about stunting. The results of the study obtained a summary result of the impact of early marriage on the incidence of stunting with a p-value of 0.02 (< α = 0.05). There is a relationship between early marriage and the incidence of stunting in the working area of the Teluk Dalam Health Center, Kutai Kartanegara Regency.